PRAKTEK PARANORMAL DALAM ISLAM (Mengidentifikasi Hadist Tentang Paranormal) - Amrullah, zen (Humanistika : Jurnal Keislaman, 2017)
Abstract:A psychic is an event or ability that can not be explained logically. Examples are event possession, telepathic ability, body that is immune to weapons, the experience of entering the supernatural and so forth. An English dictionary defines paranormal as impossible to explain scientifically, which means something that can not be explained scientifically: can not be explained or understood by the principle of scientific science. The life of a diverse society of the upper classes of the middle class and lower classes in terms of seeking satisfaction will earn income or wealth can not be considered satisfied because the satisfaction will be different views or perceptions of the thoughts of each individual. Only upper and middle class are still thinking about wanting better for the wealth they get, let alone the lower classes who have certainly wanted to improve the welfare, but there are times when it happens in this day and age people want to get the results easily and not through a good business process, even now many are doing business beyond reason or outside the logic of human thinking.Keywords: Paranorma, Islam, Hadist Â